Effects of NH4CL application and removal on astrocytes and endothelial cells. Issue 1 (December 2016) - Bartolić, Miha; Vovk, Andrej; Šuput, Dušan
Abstract Background Hepatic encephalopathy (HE) is a complex disorder associated with increased ammonia levels in the brain. Although astrocytes are believed to be the principal cells affected in hyperammonemia (HA), endothelial cells (ECs) may also play an important role by contributing to the vasogenic effect of HA. Methods Following acute application and removal of NH4 Cl on astrocytes and endothelial cells, we analyzed pH changes, using fluorescence imaging with BCECF/AM, and changes in intracellular Ca2+ concentration ([Ca2+ ]i ), employing fluorescence imaging with Fura-2/AM. Using confocal microscopy, changes in cell volume were observed accompanied by changes of [Ca2+ ]i in astrocytes and ECs. Results Exposure of astrocytes and ECs to 1 – 20 mM NH4 Cl resulted in rapid concentration-dependent alkalinization of cytoplasm followed by slow recovery. Removal of the NH4 Cl led to rapid concentration-dependent acidification, again followed by slow recovery. Following the application of NH4 Cl, a transient, concentration-dependent rise in [Ca2+ ]i in astrocytes was observed. This was due to the release of Ca2+ from intracellular stores, since the response was abolished by emptying intracellular stores with thapsigargin and ATP, and was still present in the Ca2+ -free bathing solution. The removal of NH4 Cl also led to a transient concentration-dependent rise in [Ca2+ ]i that resulted from Ca2+ release from cytoplasmic proteins, since removing Ca2+ from the bathing solution and emptying intracellular Ca2+ stores did not eliminate the rise. Similar results were obtained from experiments on ECs. Following acute application and removal of NH4 Cl no significant changes in astrocyte volume were detected; however, an increase of EC volume was observed after the administration of NH4 Cl, and EC shrinkage was demonstrated after the acute removal of NH4 Cl. Conclusions This study reveals new data which may give a more complete insight into the mechanism of development and treatment of HE.